The Epidemiology of Chronic Critical Illness After Severe Traumatic Injury at Two Level–One Trauma Centers*. Issue 12 (December 2017) - Mira, Juan C.; Cuschieri, Joseph; Ozrazgat-Baslanti, Tezcan; Wang, Zhongkai; Ghita, Gabriela L.; Loftus, Tyler J.; Stortz, Julie A.; Raymond, Steven L.; Lanz, Jennifer D.; Hennessy, Laura V.; Brumback, Babette; Efron, Philip A.; et al.
Abstract : Objective: To determine the incidence and risk factors of chronic critical illness after severe blunt trauma. Design: Prospective observational cohort study (NCT01810328). Setting: Two level–one trauma centers in the United States. Patients: One hundred thirty-five adult blunt trauma patients with hemorrhagic shock who survived beyond 48 hours after injury. Interventions: None. Measurements and Main Results: Chronic critical illness was defined as an ICU stay lasting 14 days or more with evidence of persistent organ dysfunction. Three subjects (2%) died within the first 7 days, 107 (79%) exhibited rapid recovery and 25 (19%) progressed to chronic critical illness. Patients who developed chronic critical illness were older (55 vs 44-year-old; p = 0.01), had more severe shock (base deficit, –9.2 vs –5.5; p = 0.005), greater organ failure severity (Denver multiple organ failure score, 3.5 ± 2.4 vs 0.8 ± 1.1; p < 0.0001) and developed more infectious complications (84% vs 35%; p < 0.0001). Chronic critical illness patients were more likely to be discharged to a long-term care setting (56% vs 34%; p = 0.008) than to a rehabilitation facility/home. At 4 months, chronic critical illness patients had higher mortality (16.0% vs 1.9%; p < 0.05), with survivors scoring lower in general health measures ( p < 0.005). Multivariate analysis revealed age greater than or equal to 55 years, systolic hypotension less than or equal to 70 mm Hg, transfusion greater than or equal to 5 units packed red blood cells within 24 hours, and Denver multiple organ failure score at 72 hours as independent predictors of chronic critical illness (area under the receiver operating curve, 0.87; 95% CI, 0.75–0.95). Conclusions: Although early mortality is low after severe trauma, chronic critical illness is a common trajectory in survivors and is associated with poor long-term outcomes. Advancing age, shock severity, and persistent organ dysfunction are predictive of chronic critical illness. Early identification may facilitate targeted interventions to change the trajectory of this morbid phenotype. Abstract : Supplemental Digital Content is available in the text.